Reformulation of Parking Levy Management as a Good Governance Strategy to Improve Regional Original Revenue - Aryo Akbar; Efendi Ibnususilo; Moza Della Fudika; Umi Muslikhah; Surizki Febrianto (Yayasan Pendidikan Islam Almatani, 2026)
Regional levies constitute one of the strategic sources of Regional Original Revenue (ROR) that support the financing of local government administration. One type of regional levy is the parking service levy. Although it is not the primary source of levy revenue, the parking service levy in Pekanbaru City makes a significant contribution to the increase of Regional Original Revenue. This study aims to analyze the management of parking levies in enhancing Pekanbaru City’s Regional Original Revenue and to identify the obstacles encountered in their implementation. This research employs a normative legal research method using a statutory and conceptual approach, conducted through a literature review of primary and secondary legal materials. The findings indicate that increasing Regional Original Revenue from parking levies requires effective and integrated management by the relevant authorities, encompassing planning, organizing, implementation, and supervision. However, several challenges remain, including weak supervision, limited human resources, low discipline of parking attendants in remitting levies, inadequate official attributes of parking officers, and low public awareness. Therefore, strengthening the management and supervision system of parking levies is essential to optimize their contribution to Regional Original Revenue